Ultrasound Guided Peripheral Nerve Blocks in Pediatric Patients on The Basis of Anatomical Areas; Upper and Lower Extremities: A Narrative Review - Zahid Hussain Khan; Kasra Karvandian; Amir Poya Zanjani; Majid Fakhir alhamaidah (Archives of Anesthesia and Critical Care, 2017)
A real time visualization of the peripheral nerves and adjacent anatomical structures, with ultrasound guidance, represents a new developmental technique in regional anesthesia and with more significance for pediatric patients. The main goal of this review was to explain the advantages of the ultrasound to guide the peripheral nerve block in the pediatric population for upper and lower limbs surgeries, and to show if there exists any superiority of the ultrasound technique over other traditional techniques in terms of increasing the success rate or reducing the rate of complications.